Optimal Design of Planetary Gear Mechanism for Automatic Transmission - Zhang Guofen; Guo Zaiquan; Song Zhen; Liu Jinxia (Jixie chuandong)
According to the characteristics and requirements of automatic transmission planetary gear,taking equal or close strength as optimization objective,optimization model of considering to minimize gear contact fatigue stress difference and bending fatigue stress difference is built under 40 constraint conditions including keeping reasonable transmission ratio,volume decrease,etc. And optimization calculation is performed by using MATLAB. Compared to the original design,the maximum value of planetary gear contact fatigue stress and bending fatigue stress,stress difference and integral stress decrease after optimization,especially the maximum value of bending fatigue stress decrease 12. 24% and all gears root bending fatigue stress are almost the same,the optimization effects are significant. The volume of optimized planetary gear mechanism is 3. 54%smaller than the original design,and the optimal design is superior in transmission ratio,dimension and processing parameters.